STRATEGI KOMUNIKASI HUMAS DALAM PELAKSANAAN PROGRAM CORPORATE SOCIAL RESPONSIBILITY DI PT RICKY PUTRA GLOBALINDO TBK - Azzahra, Salsabila Fitri; Saleh, Amiruddin (Program Studi Ilmu Komunikasi, Universitas Muhammadiyah Bengkulu, 2025)
In the contemporary business landscape, CSR programs are essential for fostering a favorable public image. This research highlights the significance of public relations communication in aligning corporate and community interests through CSR messaging. The study aims to evaluate the public relations strategies used by PT Ricky Putra Globalindo Tbk in its CSR initiatives. A mixed-methods approach is employed, including in-depth stakeholder interviews, employee questionnaires, and relevant documentation. The analysis is framed by Berlo's SMCR model to evaluate CSR message efficacy. Findings indicate that message source credibility, clarity, relevance to social values, and appropriate communication channels are critical to successful CSR communication. A well-structured communication strategy has been shown to improve community comprehension of CSR efforts. In summary, effective public relations communication enhances CSR program implementation and fortifies the company-public relationship, serving as a crucial element for future corporate communication policy.